1988
DOI: 10.1055/s-2007-1025051
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Contribution of the Various Energy Systems During Maximal Work of Short Duration

Abstract: The aim of this experiment was to estimate the relative contribution of the various energy delivery systems during maximal exercise tests of short duration. Twenty-five males were submitted to a VO2max test and 10-, 30-, and 90-s maximal ergocycle tests. Expiratory gases were collected with a Douglas bag during the entire 30-s test and continuously monitored with an open-circuit system during the 90-s test. Estimates of the phosphagenic component represented approximately 55%-60% of the energy expenditure duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
2
10

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 4 publications
8
103
2
10
Order By: Relevance
“…The major contributors to this 10-s work performance were estimated at 53%, 44%, and 3% for the phosphagenic, glycolytic, and oxidative pathways, respectively (Serresse et al, 1988). In contrast, when performing a 90-s work performance, the major contributors to energy production were estimated at 12%, 42%, and 46% for the phosphagenic, glycolytic, and oxidative pathways, respectively (Serresse et al, 1988). When reviewing the literature, the maximal power of the ATP-PC system has been found to vary from 1-15-s (Conley, 2000;Foss & Keteyian, 1998;McArdle, Katch & Katch, 2001;Wilmore & Costill, 1999).…”
Section: Atp-pc System Supremacy In Strength Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…The major contributors to this 10-s work performance were estimated at 53%, 44%, and 3% for the phosphagenic, glycolytic, and oxidative pathways, respectively (Serresse et al, 1988). In contrast, when performing a 90-s work performance, the major contributors to energy production were estimated at 12%, 42%, and 46% for the phosphagenic, glycolytic, and oxidative pathways, respectively (Serresse et al, 1988). When reviewing the literature, the maximal power of the ATP-PC system has been found to vary from 1-15-s (Conley, 2000;Foss & Keteyian, 1998;McArdle, Katch & Katch, 2001;Wilmore & Costill, 1999).…”
Section: Atp-pc System Supremacy In Strength Testingmentioning
confidence: 99%
“…If the intensity is maximal then the duration will be short since the energy pathway will be primarily anaerobic (Adams, 2002;Foss & Keteyian, 1998;Serresse, Lortie, Bouchard, & Boulay, 1988). To illustrate this, Serresse et al (1988) demonstrated the relationship of the time course of exercise being indicative of the energy system utilized during a 10-s work performance on a cycle ergometer.…”
Section: Atp-pc System Supremacy In Strength Testingmentioning
confidence: 99%
See 3 more Smart Citations